2018
DOI: 10.1080/10717544.2018.1507060
|View full text |Cite
|
Sign up to set email alerts
|

Touch-actuated microneedle array patch for closed-loop transdermal drug delivery

Abstract: To date, only approximately 20 drugs synthesized with small molecules have been approved by the FDA for use in traditional transdermal patches (TTP) owing to the extremely low permeation rate of the skin barrier for macromolecular drugs. A novel touch-actuated microneedle array patch (TMAP) was developed for transdermal delivery of liquid macromolecular drugs. TMAP is a combination of a typical TTP and a solid microneedle array (MA). High doses of liquid drug formulations, especially heat-sensitive compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…However, stratum corneum is the biggest obstacle to skin penetration for TDDSs. To weaken the barrier effect of stratum corneum, various methods have been developed to promote skin penetration, including those changing drug properties (liposome [7], ethosomes [8], solid lipid nanoparticles [9], microemulsion and cell-penetrating peptides [10,11]), adding chemical enhancers [12] (azone [13], surfactants [14] and terpenes [15]), and applying physical means (ultrasonic import [16], laser import [17], microneedle [18] and cupping therapy [19]). Ethosomes and microneedles are both relatively effective ways to promote penetration.…”
Section: Introductionmentioning
confidence: 99%
“…However, stratum corneum is the biggest obstacle to skin penetration for TDDSs. To weaken the barrier effect of stratum corneum, various methods have been developed to promote skin penetration, including those changing drug properties (liposome [7], ethosomes [8], solid lipid nanoparticles [9], microemulsion and cell-penetrating peptides [10,11]), adding chemical enhancers [12] (azone [13], surfactants [14] and terpenes [15]), and applying physical means (ultrasonic import [16], laser import [17], microneedle [18] and cupping therapy [19]). Ethosomes and microneedles are both relatively effective ways to promote penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported the enhanced permeation of drugs into the skin by pretreatment with a solid polymer microneedle 51 . Although the preforming of holes is simple and practical, the holes in the stratum corneum are not stable 52 , 53 because of the physical closure due to the elasticity of skin tissue. Figure 2e shows the DC resistance of the arm skin of two subjects monitored during the placement and removal of a PMN.…”
Section: Resultsmentioning
confidence: 99%
“…1b and Video S1. Furthermore, owing to the recovery ability of the skin, the created microholes gradually shrink and self-heal to closure after MA removal 41 . One of the key advantages of this design is that the users can repeat the abovementioned P&R processes to reopen the microholes for a new round of drug administration, resulting in longlasting positive diffusion and active iontophoresis.…”
Section: Drug Delivery Mechanismmentioning
confidence: 99%
“…Above all, the smartphone-powered IMAP can achieve four-drug administration strategies, including drug diffusion across intact skin, drug diffusion across poked skin, drug diffusion and iontophoresis across intact skin, and drug diffusion and iontophoresis across poked skin. The administration strategy of drug diffusion across poked skin using a touch-actuated MA patch was reported in our previous work 41 . Compared with the other four administration methods, the insulin-loaded touch-actuated MA patch exhibited the best hypoglycemic effect.…”
Section: Drug Delivery Mechanismmentioning
confidence: 99%